The Politics of Bargaining as a Group - Vincent Anesi; Peter Buisseret (Center for Economic Studies and ifo Institute (CESifo), 2023)
We develop a dynamic model in which a group collectively bargains with an external party. At each date the group makes an offer to the external party (the 'agent') in exchange for a concession. Group members hold heterogeneous preferences over agreements and are uncertain about the agent's resolve. We show that all group members favor more aggressive proposals than they would if they were negotiating alone. By eliciting more information about the agent's resolve, these offers reduce the group members' uncertainty about the agent's preferences and therefore reduce the group's internal conflicts over its negotiating strategy. To mitigate the consequent risk that negotiations fail, decisive group members successively give up their influence over proposals: starting from any initially democratic decision process, the group eventually consolidates its entire negotiation authority into the hands of a single member.
Keywords: D02; D71; D78; D82; L22; 330; adverse selection; collective choice; political economy; dictatorship; bargaining